Optimizing profitability: The impact of operational efficiency and FDR from Muamalat Islamic bank - Novia Sumarni; Francisca Sestri Goestjahjanti; Tias Pramono; Wahyu Murti (Universitas Sebelas Maret, 2024)
This research examines the role of Bank Muamalat Indonesia’s (BMI) operational efficiency and Financing to Deposit Ratio (FDR) in affecting its profitability. This topic becomes more important considering the issue of the bank being hit by a drastic decline in profits. Collected data from quarterly financial reports published on the BMI's official website from 2013 to 2023, covering 44 observation periods. The data were analyzed using SPSS 27. The results indicate the negative effect of BOPO and the positive effect of FDR on ROA. Indicates that operational inefficiencies will suppress profitability. On the other hand, through increased funding distribution, banks will also benefit from the profit sharing obtained. So, if a bank wants to increase profitability, the two methods are operational efficiency and increasing FDR. This result suggested that Islamic banks must manage their operational income while controlling their operation costs to maintain operational efficiency. Also advised to maintain their bank’s performance by observing the financing options they offer for their customers. This finding is also expected, especially for policyholders at BMI, as an essential implication for getting out of the difficult situation.